Injuries from border wall falls after 2018 are more severe: a retrospective cohort study - Gregory H. Whitcher; Susan F. McLean (Injury Epidemiology, 2024)
Abstract Background The U.S.-Mexico “border wall” between El Paso, Texas and Ciudad Juárez, Mexico was raised and extended beginning in 2018 in accordance with Presidential Executive Order 13,767. We hypothesized that these changes resulted in increased incidence and severity of injuries of individuals attempting to cross the border wall in the El Paso region. Methods A retrospective cohort review was conducted of University Medical Center of El Paso Trauma Registry charts from 2001 to 2022. Year of injury, gender, age, Injury Severity Score, hospital length-of-stay, ICU length-of-stay, ventilator days, and survival were analyzed by Chi-square analysis with Fisher’s exact test for categorical variables and Independent Samples T-test for continuous variables. An independent samples Mann Whitney U Test was used to compare border wall fall injuries before and after 2018. Results Of the 842 patients reviewed, 69 patients presented before 2018 and 773 presented from 2018 to 2022. Statistically significant differences were identified in the mean Injury Severity Score which increased from 6.3 (SD ± 3.8) to 8.3 (SD ± 5.5, p < .001) and the mean hospital length-of-stay which increased from 6.7 days (SD ± 5.5) to 9.5 days (SD ± 8.0, p < .005). Conclusion The incidence, severity, and hospital length-of-stay related to injuries crossing the U.S.-Mexico border have increased with changes in height of the border wall since 2018. Additional resources should be allocated to Emergency Departments and Trauma Centers along the Southwest Border to serve this unique patient population. Additional consideration should be given to the cost of the border wall.